Cure of murine leishmaniasis with anti-interleukin 4 monoclonal antibody. Evidence for a T cell-dependent, interferon gamma-independent mechanism (The Rockefeller University Press, 1990)
BALB/c mice infected with Leishmania major develop fatal, progressive disease, despite an immune response characterized by expansion of CD4+ T cells in the draining lymph nodes. The immune response has been further characterized by a lack of IFN-gamma mRNA, but increased IL-4 mRNA in lymphoid tissues, and striking elevation of serum IgE. Treatment of infected BALB/c mice with rIFN-gamma at doses shown to be beneficial in other protozoan infections was insufficient to ameliorate L. major infection. In contrast, neutralization of IL-4 by six weekly injections of mAb 11B11 led to attenuation of disease in 100% of animals, and complete cure in 85%. Resolution of disease required the presence of T cells, and recovered mice remained resistant to reinfection at 12 wk. This immunity was adoptively transferable and was dependent on both CD4+ and CD8+ cells. Although administration of anti- IL-4 was associated with fourfold increase in IFN-gamma mRNA in lymph node cells draining the lesion, the coadministration of neutralizing R4 6A2 anti-IFN-gamma mAb had no effect on resistance to disease. This was in marked contrast to resolution of disease in both resistant C57BL/6- and GK1.5-pretreated BALB/c mice that was abrogated by in vivo treatment with anti-IFN-gamma. These data suggest a novel mechanism of cellular immunity established by interference with the development of Th2 cells during infection.